Dual Key Authentication Model with Cryptography enabled Data Transmission Model in Smart Cities - V.Pavani,; V.Lakshman Narayana,; Suryaprakash Nalluri,; Adapa Srinivasa Rao,; Murali Mohan Malyala, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The high pace at which smart cities are developing introduce numerous challenges which should be addressed to fully secure all interconnected and data-driven infrastructure. The security aspect mandates a more advanced security paradigm which would help keep all sensitive information within the jurisdiction of its creators and ensure secure communication between all devices. Thus, this research will advance a dual-key authentication model designed to ensure the safeguarded transmission of data within smart cities by including asymmetric encryption. The model is designed to advance a security paradigm which bases the security of the well-proven efficiency of symmetric encryption of the data which is then distributed among authorized users and the optimal security in case of asymmetric encryption for key exchange and user authentication. Specifically, the data is encrypted by a symmetric key and then roasted across the authorized bridge to the nearest authorized user. The key used to encrypt the data is shared through public medium and private key is securely maintained. Therefore, the symmetric key which is raised to transfer the data across the bridge is encrypted using the public key before sending it to a remote user who decrypts using their private key. Asymmetric encryption is optimal for sending a symmetric key because it is subjected to encryption algorithms which utilize symmetric encryption execute faster and are more economically viable thus optimal for transferring large volumes of data fast. This research proposes a Dual Key Authentication Model with Cryptography enabled Data Transmission Model in Smart Cities (DKAM-CDTM). Since the data is sent across the bridge, while asymmetric encryption is optimal for key exchange, authentication and transmission. Therefore, the model will mitigate against the most common security vulnerabilities in smart city context including interception and acquisition of the key, hacking into the system and key management. It secures the transmission and utilization of the key. Finally, the proposed model will be tested through a simulation to establish the encryption of the time taken to secure data, and authenticate potential security threats. The factorial tests conducted applications that have proven that the dual-key is by fact an optimal way of transferring data in a smart city. The proposed model achieved 98.8% accuracy in Dual Key Authentication, 98.9% accuracy in Key Generation and 99.4% accuracy in providing Data Security. The proposed model efficiently provides security to the smart city model that is used for secure data transmission.